NAVIGATING CHALLENGES IN CARBON CYCLE POOL-AND-FLUX REASONING: UNDERSTANDING AND RESPONDING TO STUDENTS' NEEDS (International Journal of Food and Nutritional Sciences, 2022)
Pool-and-flux reasoning for the carbon cycle is an essential component of climate literacy. The first part of this essay discusses the significance and difficulty of this kind of thinking. Two studies' worth of results are presented. The first explains the methods used by students to apply pool-and-flux logic to the carbon cycle. The second discusses and presents findings from a model-based pooland-flux reasoning educational intervention for secondary pupils. Prior to receiving training, the majority of secondary students used heuristics for informal reasoning in solving carbon cycle pool-and-flux questions, such as good vs poor and correlation heuristics. Following education, the percentage of students using pool-and-flow reasoning based on goal models rose from 27 to 52 percent. This study provides a viable teaching strategy for facilitating advances in students' modelbased pool-and-flux reasoning by building on earlier and current research.